Is Irish innovation policy working? evidence from Irish technology businesses - Jordan, D.; O'Leary, Eoin (Statistical and Social Inquiry Society of Ireland, 2008)
In the last decade Irish innovation policy has been focused on Higher Education Institutions (HEIs). This paper explores the effects of HEIs, in the context of interaction with other interaction agents, on the innovation output of Irish high-technology businesses. Based on a survey of 184 businesses in the Chemical and Pharmaceutical, Information and Communications Technology and Engineering and Electronic Devices sectors, the paper estimates the importance of in-house R&D activity and external interaction with HEIs, support agencies and other businesses for product and process innovation. A key finding is that the greater the frequency of direct interaction with HEIs the lower the probability of both product and process innovation in these businesses. There is some evidence of a positive indirect HEI effect, through complementarities of interactions with suppliers and support agencies. However, while external interaction is important for innovation output, there is little evidence that geographical proximity matters. These findings have important implications for Irish innovation policy. Last year`s Strategy for Science, Technology and Innovation: 2006 to 2013 committed an additional ?1.88 billion for research and commercialisation programmes in HEIs. The econometric results presented suggest that this substantial public investment in HEIs may have a disappointing, and perhaps even a negative, effect on the innovation output of Irish business, thus undermining future Irish prosperity. In addition, the absence of evidence supporting the existence of Irish clusters and networks for innovation suggests that policymakers long-standing support for these have been misguided. The paper concludes by advocating that innovation is a business rather than a technological phenomenon and argues for a changed role for HEIs to one of responding to innovative businesses.
read before the Society, 25 October 2007
Keywords: Innovation; Research and development; Interaction; Innovation policy; 314.15